Prof. M.S. Pavgi Award Lecture - Red rot of sugarcane - Current Scenario - SATYAVIR - SATYAVIR, SATYAVIR (Indian Phytopathology, 2003)
At the outset, I wish to convey my gratefulness to Indian Phytopathological Society for inviting me to deliver this prestigious Prof. M.S. Pavgi Award Lecture-2002. I feel humbled to deliver this lecture, which is named after this great doyen of Mycology. I do recall my days in IARI when as a postgraduate student, I had an exhaustive exposure to outstanding research contributions of Prof. M.S. Pavgi in the area of Mycology. It is, therefore, my distinct privilege and a pleasure to deliver this coveted Award Lecture.